Meta-QTLs para resistência a antracnose (Colletotrichum lindemuthianum) e expressão diferencial de genes durante interação com a raça 65 no feijoeiro (Phaseolus vulgaris l) - Miguel, Luciana Aparecida (2020)
The common bean (Phaseolus vulgaris L.) is one of the most important direct consumption legumes in different parts of the world, and this is due to the fact that its grain provides easy access to proteins and minerals, mainly in developing countries. Crop production can be affected by different types of pests and pathogens. Among them, Anthracnose, a fungal disease caused by Colletotrichum lindemuthianum and one of the most economically important diseases, which can lead to severe losses in productivity, under favorable conditions. Due this situation and considering the amount of available information for genetic control of the disease, the aim of this project was (i) To perform a meta-analysis of QTLs that confer resistance to anthracnose, searching for resistance genes in the smallest confidence interval and (ii) Validate the expression oftwo indicated disease resistance genes, using the semi-quantitative PCR technique. The meta-analysis was able to gather information on several cultivars that presented an effective resistance to different pathogen races, showing some stable QTLs distributed over the 11 chromosomes, however not all QTLs were considered. Also, from this study it is possible that breeding programs can perform a pyramiding of resistance genes, ensuring the long-lasting resistance. It is important to note that this QTLs meta-analysis can be refined with data from later studies, in order to contribute to obtain new resistant cultivars to various anthracnose races. Analysis of two candidate genes expression via semi-quantitative PCR revealed that there wasn't differential expression between the resistant and susceptible inoculated cultivars with Colletotrichum lindemuthianum, however, it is necessary to perform more in-depth studies using sensitive techniques to quantify gene expression.